Superacids Based on Pentafluoroorthotellurate Derivatives of Aluminum. Issue 28 (30th May 2017) - Wiesner, Anja; Gries, Thomas W.; Steinhauer, Simon; Beckers, Helmut; Riedel, Sebastian
Abstract: The new Lewis acid Al(OTeF5 )3 and its acetonitrile adduct CH3 CN→Al(OTeF5 )3 were obtained by a simple one‐step synthesis in batches of up to 15 g. Al(OTeF5 )3 and the adduct were characterized by vibrational spectroscopy (IR, Raman) and quantum‐chemical calculations. Furthermore, five different salts of the new weakly coordinating anion [Al(OTeF5 )4 ] − were prepared in a two‐step procedure. [Ph4 P][Al(OTeF5 )4 ], Cs[Al(OTeF5 )4 ], [Ph3 C][Al(OTeF5 )4 ], as well as the protonated benzene derivatives [C9 H13 ][Al(OTeF5 )4 ] and [C6 H7 ][Al(OTeF5 )4 ] were characterized by low‐temperature single‐crystal X‐ray diffraction and NMR spectroscopy. Arenium salts have rarely been characterized in the solid state and were synthesized in this work in a simplified fashion. Abstract : Novel superacids : New Brønsted as well as Lewis superacids based on pentafluoroorthotellurates have been synthesized. The corresponding weakly coordinating anion has been used to stabilize carbocations, for example.